EXPERIMENTAL STUDY OF THE EFFECT OF SIO2 ON NI SOLUBILITY IN SILICATE MELTS - Borisov A.A. (My University, 2006)
The solubility of Ni in silicate melts with variable SiO2 content was studied at a total pressure of 1 atm within a wide range of temperature and oxygen fugacity. The maximum solubility of Ni (minimum activity coefficient of NiO) was observed in melts with ~ 55-57 wt % SiO2, regardless of temperature and oxygen fugacity. Melts beyond this range showed significantly lower Ni solubility and, correspondingly, higher NiO activity coefficients. The analysis of our results and literature data led us to the conclusion that the NBO/T (number of nonbridging oxygen atoms per tetrahedrally coordinated atom) is inadequate to describe the effect of melt composition on Ni solubility. © Nauka/Interperiodica 2006.